Kinetic modelling of free-radical vinyl chloride polymerization with a mixture of initiators - Tan , Amy Siew Wern (Penerbit UTM Press, 2008)
The most critical unit operation in commercial manufacturing of poly(vinyl chloride) (PVC) is the polymerization reactor. Therefore, application of modelling techniques on polymerization reactors is essential to gain a clear understanding on the polymerization kinetics. In this paper, the kinetic behaviour of free-radical vinyl chloride polymerization in a suspension poly(vinyl chloride) (PVC) reactor is described. A kinetic model is used to describe the polymerization reaction. The isothermal model predicts the overall monomer conversion, the polymerization rate, reactor pressure and the monomer distribution in the gas, aqueous, and polymer phases for the polymerization cycle. In commercial reactors, mixtures of initiators are usually added to increase the polymerization rate. The model also explores the effect of initiators onto the polymerization rate and conversion. All algorithms are written in MATLAB 7.1.